Syntaxonomy and ecology of plant communities of the Carici rupestris-Kobresietea bellardii in the western carpathians - Petrik, Anton; Dubravcova, Zuzana; Jarolimek, Ivan; Kliment, Jan; Sibik, Jozef; Valachovic, Milan (Biológia, 2006)
We present a syntaxonomic account of the communities of the alliances of Oxytropido-Elynion Br.-Bl. 1949 and Festucion versicoloris Krajina 1933 from Western Carpathians. Both alliances comprise naked-rush, cushion form and dwarf-shrub heath communities typical of wind-exposed habitats occurring at the highest altitudes of the Tatra Mts. They represent a relic vegetation of the cold stages of the Pleistocene (probably Late Glacial Maximum) and they can be classified within the class of Carici rupestris-Kobresietea bellardii Ohba 1974. A set of relevÃ©s was subject to numerical-classification analysis. Floristics and ecology of the communities were characterised and the relationships to similar syntaxa were discussed.The Oxytropido-Elynion is restricted to the extreme ridge positions in the highest altitudes of the Belianske Tatry Mts. Five associations were distinguished, such as the Pyrolo carpaticae-Salicetum reticulatae, the Festuco versicoloris-Oreochloetum distichae, the Festucetum versicoloris, the Oxytropido carpaticae-Elynetum myosuroides and the Drabo siliquosae-Festucetum versicoloris.The Festucion versicoloris is limited to the mylonite zone of the alpine and subnival belt of the VysokÃ© Tatry and ZÃ¡padnÃ© Tatry Mts (and found as rare in the NÃzke Tatry Mts). The stands of these communities prefer terraces of steep rocky faces and cliffs and stabilised small-grained screes below the cliffs. Within this alliance, three associations were described, including the Agrostio alpinae-Festucetum versicoloris, the Silenetum acaulis and the Salicetum kitaibelianae.